O pedagogo na efetivação do currículo integrado na educação profissional e tecnológica de nível médio (EPTNM). - Memória, Francilene da Silva (2020)
The study emerged from the inquiries concerning the practice of the pedagogue in the scope of the Federal Institutes, concerning the effectiveness of the Integrated Curriculum in the EPTNM. The research is nucleated in Line 02 of the Professional Master in Professional and Technological Education - "Organization and Memories of Educational Spaces in EFA" and is linked to macro-project 06 - "Organization of Educational Spaces in EFA". The problem raised in the research was: What are the main conceptions of the pedagogues in front of the effectiveness of the Integrated Curriculum in the EPTNM in the scope of the Federal Institute of Amazonas (IFAM) Campus East Zone (CMZL)? The general objective of this work was to investigate the activity of the pedagogue in the implementation of the Integrated Curriculum at the Federal Institute of Education, Science and Technology of the Amazonas Campus East Zone (IFAM-CMZL) which has as specific objectives: To discuss the principles of the Integrated Curriculum at the EPTNM; To identify the conceptions of the Integrated Curriculum present in the pedagogical work of the pedagogue at the EPTNM and; To propose the construction of an informative guide that deals with the pedagogical work of the pedagogue in the implementation of the Integrated Curriculum at the EPTNM. They composed the sample universe of the research 04 (four) subjects: 03 (three) pedagogues working in the Integrated High School and 01 (one) pedagogues working in Proeja. As a research strategy, the case study was used. The observation associated with the semi-structured interview was applied as a data collection instrument. All the statements, transcribed from the interviews, were submitted to content analysis: pre-analysis, exploration of the material, and treatment of the results (BARDIN, 2009). The results obtained were supported by a concise theoretical basis with the theme worked on: Saviani (1994; 2007); Moura (2007); Ramos (2008; 2011; 2014), among others. The results indicated that the pedagogue is inserted as an agglutinating agent in the teaching and learning process, since its dynamics, organization, means, and objectives are built from real contexts, many times escaping from its control or desire, due to the simple fact of the multiple dimensions that the pedagogical act demands. Those researched recognize themselves in the process of implementing the Integrated Curriculum and see limitations in the implementation of new ideas, in the face of immediate realities that arise in the school environment. However, the subjects of the research understand the importance of their action in the educational processes, mainly to help teachers, from the articulation of contents, methods, and techniques, to the transposition of real teaching and learning situations. The need for curricular and formative updating, within the training centers, as well as in the labor scope of this professional, given the changes inherent to EFA, is also highlighted. As an unfolding of the research, an educational product was built, in the format of the Guide "Paths to Effective Integrated Curriculum in Professional and Technological High School Education (EPTNM): The Importance of the Pedagogue", which has the function of indicating alternatives for the effectiveness of the Integrated Curriculum, having as a focus pedagogues acting in the RFEPT and related professionals.